PERTUMBUHAN EMPAT POPULASI CEMPAKA (Michelia champaca Linn.) UMUR EMPAT TAHUN (Growth of four populations of cempaka (Michelia champaca Linn.) at four years old) - Murniati Murniati; Hani S. Nuroniah; Darwo Darwo (Jurnal Penelitian Hutan Tanaman, 2019)
ABSTRACTEx-situ conservation is highly beneficial in protecting biodiversity, especially to save certain species from extinction. Cempaka (Michelia champaca Linn.) is a tree species that is getting rare as its natural population at some areas were difficult to be discovered. Cempaka tree produces not only wood, but also flowers that can be used for perfumery raw materials and essential oils. Therefore, cempaka species needs to be conserved, either through in-situ or ex-situ method. In order to support ex-situ conservation, a plot of cempaka was established in 2011 at Pasir Hantap Research Forest, Sukabumi District-West Java. The genetic materials were collected from four populations, consisted of 42 mother trees divided by Lahat population (9 mother trees), Empat Lawang population (6 mother trees), Malang population (13 mother trees), and Pasuruan population (14 mother trees). Sub plots were designed based on the seedlings origin (population) and distance among sub plots were ≥ 50 m to avoid cross pollination among populations. The plots were maintained regularly, including weeding, fertilizing, and pest control. Growth observation of cempaka plants was conducted every six months up to 36 months old and then every one year afterwards. The observation consists of survival rate, height and diameter of cempaka stems. Average survival of cempaka plants at 48 moths old was 82.4%, the highest survival was found at Lahat population (94.8%). The highest height and diameter were found at Lahat population as well, i.e. 7.35 m and 13.1 cm, respectively. The lowest survival rate was found at Malang population (64.0%), meanwhile the lowest height and diameter growth were found at Pasuruan provenance, i.e. 2.99 m and 3.9 cm, respectively. It can be concluded that the highest growth, meaning its best performance of cempaka plants was shown by Lahat provenance. It implies that characteristics of mother trees and the seed quality gave a significant effect to the cempaka plant growth. ABSTRAKKonservasi ex-situ berfungsi untuk melindungi biodiversitas, terutama jenis-jenis yang terancam punah. Cempaka (Michelia champaca Linn.) termasuk dalam jenis yang semakin jarang ditemukan di populasi alaminya. Selain dimanfaatkan kayunya, bunga cempaka dipanen sebagai material parfum dan minyak. Sebagai salah satu upaya konservasi ex-situ, plot cempaka dibangun pada tahun 2011 di Hutan Penelitian Pasir Hantap, Sukabumi-Jawa Barat. Material genetik (biji) dikoleksi dari empat populasi cempaka yaitu dari 42 pohon induk yang terdiri atas : Lahat (9 pohon induk), Empat Lawang (6 pohon induk), Malang (13 pohon induk), dan Pasuruan (14 pohon induk). Plot penanaman dirancang berdasarkan asal populasi, selanjutnya jarak plot antar populasi minimal 50 m untuk menghindari terjadinya persilangan antar populasi. Pemeliharaan plot dilakukan secara berkala meliputi penyiangan, pemupukan dan pengendalian hama penyakit. Pengukuran performa pertumbuhan dilakukan setiap 6 bulan hingga umur 36 bulan setelah tanam; dan satu tahun sekali setelahnya. Performa pertumbuhan yang diamati meliputi daya hidup, tinggi dan diameter batang diatas tanah. Daya hidup cempaka pada umur 48 bulan rata-rata sebesar 82,4% dan daya hidup tertinggi ditunjukkan oleh cempaka dari populasi Lahat (94,8%). Tinggi dan diameter tertinggi ditunjukkan oleh cempaka dari populasi Lahat yaitu 7,35 m dan 13,1 cm. Daya hidup terendah ditemukan pada cempaka populasi Malang (64,0%). Tinggi dan diameter pohon terendah teramati pada cempaka populasi Pasuruan yaitu 2,99 m dan 3,9 cm. Populasi terbaik berdasarkan pengamatan performa pertumbuhannya ditunjukkan oleh populasi Lahat. Dari penelitian ini dapat disimpulkan bahwa karakteristik pohon induk dan kualitas benih cempaka berpengaruh terhadap pertumbuhan tanaman cempaka.